Corrections on the notes of the group-genus theronia (hymenoptera:inchneumonidae:pimplinae)of Malaysia. - Amanda , T.P.O.; Ng, Y.F; Idris, A.B (Pusat Sistematik Serangga ,UKM, 2011)
A preminary taxonomic study of the group-genus of theronia (hymenoptera; ichneumonidae; pimplinae) from Malaysia was conducted in 2008 and atotal of five subgenera and 19 species were identified then.However, after a thorough study was done in 2009, we found that there are some misidentifications of species.Five species were misidentified and corrected giving a total of five genera and 13 species instead of 19 species.Hence,only two new records for Malaysia are recognized instead of eight as written in Serangga 13(1-2);19-37